HUBUNGAN KONSEP SETING FISIK DAN KONSEP PERILAKU DI AREA DEPAN GEDUNG REKTORAT Studi Kasus: Universitas Negeri Yogyakarta - Adimas Kristiadi (ATRIUM: Jurnal Arsitektur, 2016)
Title: The Relation of Physical Setting Concept and Behavior Concept in the Front of Rectorate Building, Case Study: Yogyakarta State University Students are the "actors" in the university because of their activities. Students need a certain space in the environment around the university. It becomes interesting when students do their activities around the building that is also the environment for rector and university employees, those happened at the area in front of Yogyakarta State University (UNY) rectorate building. There was a cozy quality (fit) space in there based on perception (cognition and schemata) and adaptation of UNY students for area of the UNY rectorate building. There were some quality factors (property) which is included as environment (physical setting) that affect the activity (behavior) of UNY students. The correlation between activity (behavior pattern) and specific environmental order (physical setting) interpreted as behavior setting. The method used is deductive-qualitative with rationalist paradigm. The data obtained were the result of observation, behavior mapping, interviews, questionnaires, with induction analyzed. The results are: 1) the vertical property provided physical comfort and social comfort; 2) the proximity property provided environmental comfort; 3) the artificial lighting distribution property provided social comfort; 4) the property of which describes the situation of natural protection provided physical comfort and environmental comfort.